WHAT DRIVES IN-APP PURCHASE INTENTION FOR LOOT BOX IN MOBILE GAMES? - Khodiyat, Andre; Aprilianty, Fitri (Journal of Business and Management, 2018)
Abstract. Mobile games, an often-overlooked, lucrative market, is currently experiencing an uptrend. Old models of monetization, in which the user pays for the game, are being scrapped. New models, freemium, which implement in-app purchases on a free game, are more opted. These models are proven to be quite successful, generating massive amount of revenue currently exceeding standard priced games. A newer, latter addition of the in-purchases model in mobile games, loot boxes are on the rise, while generating profit and controversy consecutively. Controversy, associations, and mixed dispositions of the matter are growing. Some gamers despised it, by stating it on forums or articles, while game developers actively defend the system as it has generated a reliable and legal source of income. Game developers will not discontinue the system as it is very lucrative, however growing negative disposition from netizen and gamers alike might make the matter problematic. Few studies have taken place on the matter; hence, the purpose of the study is to examine gamers’ perception loot box in-app purchases, asses the relationship between gamers perception of mobile games and loot box towards the purchase intention of loot boxes, and finally, investigate the motivation of gamers to purchase loot box as an in- app purchase. This research utilizes qualitative method, unstructured interview for its research. Then variable defined from qualitative and literature review are further measured with quantitative methods, survey questionnaires. Data analysis are conducted with Partial Least Sqaures, using SmartPLS due to exploratory nature of the research, and the multitudinous, some untested variables. This research found the major influence of perception on mobile game particularly monetary value as value for money and social value towards loyalty and purchase intention. Motivation also has an effect on purchase intention stemming from game design on social interaction. Results: After eliminating unreliable indicators, unreliable variables, and analyzing model fit, several variables show valid and significant correlations. Perceived value on mobile games does have a positive impact on purchase intention, namely value for money towards purchase intention, which indicated a major path coefficient of 0.31. While, emotional value (β=0.46), social value (β=0.20), and value for money (β=0.18) exhibited impact on loyalty. Qualitative research indicated five variables from loot box perception: loot box value for money, loot box performance/quality value, loot box emotional value, loot box alternatives, and suspicion on loot box as developer’s money making scheme. However from further quantitative method and analysis, the result indicated loot box emotional value effect towards purchase intention (β=0.20) and loot box performance/quality value towards loyalty (β=0.12). Motivation also exhibit effect on purchase intention, particularly social interaction role on purchase intention (β=0.48), which indicates a large degree of magnitude. Conclusion: Purchase intention can be influenced by perception either directly or through loyalty. Perception in perceived value of its self are the perceived value of something received (social value, emotional value, loot box performance/quality value) in return for something given (value for money). Enhancement on both ends of the perception will increase perceived value and affect either purchase intention, loyalty, or both. Hamari et al. (2017) provided a model for in-app purchase motivation, which stated that motivation stems from design decisions by developers that entice players to purchase mediated by this design implementation. In this study, in regard with the game Mobile Legends: Bang Bang, one design decision are exhibited, social interactions.Keywords: loot box, in-app purchase intention, Mobile Games, motivation, perception